Fabrication of black NiO/Sr2FeTaO6 heterojunctions with rapid interface charge transfer for efficient photocatalytic hydrogen evolution - Yu, Guiyun; Hu, Jiawei; Xiao, Wen; Zhu, Yongtai; Dai, Yong (Frontiers in Chemistry, 2023)
Series of black NiO/Sr2FeTaO6 (NiO/SFT) composites were synthesized by the combined processes of hydrothermal method and calcination treatment. The formed NiO was deposited on the surface of Sr2FeTaO6 to form a closely interfacial contact, leading to the formation of NiO/Sr2FeTaO6 heterojunction. The resulted samples were fully characterized by XRD, TEM, XPS, and UV-Vis DRS to gain their microstructure, crystal phase, atomic states and optical absorption properties. Introducing narrow-bandgap semiconductor of black NiO in NiO/Sr2FeTaO6 heterojunctions exhibits two major advantages. On the one hand, coupling with black NiO can significantly increase the light harvesting capacity of Sr2FeTaO6. On the other hand, the formed NiO/Sr2FeTaO6 heterojunctions benefited the separation and transfer of photogenerated charge carriers, which was confirmed by photo-electrochemical measurement, PL and TR-PL spectra. The activity of as-prepared samples was evaluated by photocatalytic hydrogen (H2) evolution (PHE) under visible light irradiation. The resulted NiO/SFT composites showed the improved PHE efficiency than that of NiO and Sr2FeTaO6, owing to the synergistic effects of synergistic effects of heterojunction formation for the efficient charge carrier transfer/separation and increased light harvesting capacity. However, the excess amount of NiO loaded in NiO/SFT composites will restrain the light harvesting of Sr2FeTaO6 component and decrease, leading to the decreased PHE activity. Our work provided an insight on the construction of high-efficiency heterojunction photocatalysts for PHE reaction.